Introduction to the Special Issue on Cognitive and Behavioral Flexibility in Fear and Anxiety Disorders. Issue 6 (November 2018) - Boisseau, Christina L.; Garnaat, Sarah L.
Converging lines of research highlight the significance of cognitive and behavioral flexibility in the etiology, maintenance, and treatment of fear and anxiety disorders. We have developed a Special Issue to highlight recent empirical investigations, contemporary theory, and novel directions for future study. It is hoped that this special issue will (a) underscore the centrality of cognitive and behavioral flexibility to fear- and anxiety-related psychopathology, (b) call attention to cognitive science approaches investigating related neuropsychological correlates, and (c) highlight novel experimental and theoretical research on germane contextual factors.